Metastatic implantation of oral cancer in forearm: An unusual presentation (Indian Journal of Case Reports, 2020)
Metastatic implantation of cancer cells at a free flap graft donor site is a very unusual presentation. The possible mechanism is accidental contamination of the graft site by instruments used for surgery on the primary site. The other potential causes are the hematogenous spread of the tumor and de novo tumorigenesis. This report describes the case of a 65-year-old gentleman with carcinoma of the left buccal mucosa, which underwent wide local excision of the growth with type III modified radical neck dissection with radial forearm free flap reconstruction and subsequently developed a metastatic nodule over the graft donor site after 3 months. The nodule was excised with an adequate margin after which the patient refused to undergo any further treatment. Proper care taken while dealing with the tumor as well as the graft donor site shall avoid such iatrogenic complications due to possible accidental contamination of the graft donor area.